2014
DOI: 10.1136/annrheumdis-2013-204906
|View full text |Cite
|
Sign up to set email alerts
|

Aiming for SDAI remission versus low disease activity at 1 year after inclusion in ESPOIR cohort is associated with better 3-year structural outcomes

Abstract: Aiming for SDAI remission rather than LDA at 1 year leads to better radiographic outcomes at 3 years in early RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
(23 reference statements)
2
13
0
1
Order By: Relevance
“…Also under evaluation is the contribution of biologics, particularly TNF␣ antagonists, which were used during the first five years in about 22% of ESPOIR patients with RA. Several studies evaluated management strategies for recent-onset RA [23,[46][47][48][49][50][51]53]. The results confirmed the beneficial effects of early rheumatologist referral of patients with early arthritis; early administration of effective DMARD therapy, which decreased 1-year radiographic progression when started within three months after disease onset; and tight disease control based on a validated activity score to allow prompt treatment adjustments.…”
Section: Treatments and Management Strategiessupporting
confidence: 70%
See 1 more Smart Citation
“…Also under evaluation is the contribution of biologics, particularly TNF␣ antagonists, which were used during the first five years in about 22% of ESPOIR patients with RA. Several studies evaluated management strategies for recent-onset RA [23,[46][47][48][49][50][51]53]. The results confirmed the beneficial effects of early rheumatologist referral of patients with early arthritis; early administration of effective DMARD therapy, which decreased 1-year radiographic progression when started within three months after disease onset; and tight disease control based on a validated activity score to allow prompt treatment adjustments.…”
Section: Treatments and Management Strategiessupporting
confidence: 70%
“…The results confirmed the beneficial effects of early rheumatologist referral of patients with early arthritis; early administration of effective DMARD therapy, which decreased 1-year radiographic progression when started within three months after disease onset; and tight disease control based on a validated activity score to allow prompt treatment adjustments. The need to achieve an early clinical remission in order to prevent and limit the development of midand long-term complications has been convincingly demonstrated [22,53] and constitutes additional scientific support for the latest recommendations on managing RA [55,56]. Finally, management strategies currently used in everyday practice are not always fully consistent with clinical practice [47].…”
Section: Treatments and Management Strategiesmentioning
confidence: 93%
“…An interesting definition for daily practice is ‘the absence of signs and symptoms of significant inflammatory disease activity’ 11. Recent evidence has suggested that remission leads to a better outcome than low disease activity (LDA),62 64 65 and the committee was of the opinion that clinical remission according to the ACR-EULAR Boolean or index-based definition is the target for every patient presenting with early arthritis. A LDA state could be an appropriate alternative goal only in cases in which remission is considered unfeasible.…”
Section: Resultsmentioning
confidence: 99%
“…Very little disease progression occurred as long as patients were in remission according to the Simplified Disease Activity Index or the Clinical Disease Activity Index. Again, in this study there was slightly more RP in those patients taking DMARD compared to those receiving biologics 17 .…”
mentioning
confidence: 75%